Позиционирование изображений фотошаблонов в системах автоматизированного оптического контроля - Krylov, V. N.; Shcherbakova, G. Yu.; Kozina, Yu. Yu. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
An automated optical positioning system for photomasks of integrated circuits has been developed. The image processing methods are based on hyperbolic wavelet transforms and the calculation of geometric moment features of fiducial marks. The system demonstrates high noise immunity and accuracy.